2023
DOI: 10.3390/ijms241713269
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Breast Cancer LCK Proto-Oncogene as a Master Regulator of TNBC Neutrophil Enrichment and Polarization

Fatma Al Qutami,
Walaa Al Halabi,
Mahmood Y. Hachim

Abstract: The role of neutrophils in breast cancer shows that the N1 proinflammatory subtype can suppress and attack the tumor. In contrast, the N2 pro-tumor subtype aids the tumor in its survival, progression, and metastasis. Recently, more focus has been directed to the role of innate myeloid cells, specifically neutrophils, in regulating the responses of lymphoid populations both in the progression of cancer and in response to therapy. However, the exact crosstalk between breast cancer cells and neutrophils is poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In this study, 101 DEGs associated with BRCA inflammation, including 55 upregulated genes and 46 downregulated genes, were identified by analyzing TCGA-BRCA data. Univariate analysis and bioinformatics analysis revealed that the effects of the BST2 [ 31 ], CXCL6 [ 32 ], GPR132 [ 33 ], IL12B [ 34 ], IL18 [ 35 ], IL1R1 [ 36 ], IL2RB [ 37 ], IRF1 [ 38 ], IRF7 [ 39 ], KCNMB2 [ 40 ], LCK [ 41 ], RGS1 [ 42 ], SELL, TACR1, TAPBP and TNFRSF1B [ 43 ] genes on the prognosis of patients with BRCA were significant, and a search of the literature revealed that some of the 16 genes are therapeutic targets and risk predictors for BRCA [ 44 , 45 ]. A prognostic model for the 16 inflammatory genes was constructed, and the predictive ability of this prognostic model was verified, highlighting the prognostic survival curves and plots containing 16 gene signatures and clinicopathological parameters showing great prognostic efficacy, which might allow clinicians to make judgments about outcomes for individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 101 DEGs associated with BRCA inflammation, including 55 upregulated genes and 46 downregulated genes, were identified by analyzing TCGA-BRCA data. Univariate analysis and bioinformatics analysis revealed that the effects of the BST2 [ 31 ], CXCL6 [ 32 ], GPR132 [ 33 ], IL12B [ 34 ], IL18 [ 35 ], IL1R1 [ 36 ], IL2RB [ 37 ], IRF1 [ 38 ], IRF7 [ 39 ], KCNMB2 [ 40 ], LCK [ 41 ], RGS1 [ 42 ], SELL, TACR1, TAPBP and TNFRSF1B [ 43 ] genes on the prognosis of patients with BRCA were significant, and a search of the literature revealed that some of the 16 genes are therapeutic targets and risk predictors for BRCA [ 44 , 45 ]. A prognostic model for the 16 inflammatory genes was constructed, and the predictive ability of this prognostic model was verified, highlighting the prognostic survival curves and plots containing 16 gene signatures and clinicopathological parameters showing great prognostic efficacy, which might allow clinicians to make judgments about outcomes for individual patients.…”
Section: Discussionmentioning
confidence: 99%